Modeling of the Interface of Functionally Graded Superelastic Zones in Compliant Deployable Structures - Jovanova, Jovana; Domazetovska, Simona; Frecker, Mary (American Society of Mechanical Engineers, 2018)
Functionally graded compliant mechanisms can be fabricated with additive manufacturing technology by engineering the microstructural and compositional gradients at selected locations resulting in compositionally graded zones of higher and lower flexibility. The local compliance depends on the geometry of the structure as well as the material property in the selected region. As Nitinol (NiTi) is well suited for applications requiring compliance, the critical transformation stress and the superelastic modulus of elasticity are crucial parameters for defining the local compliance. To understand the behavior at the interface between two different material compositions, three models of gradient change between the alloys are analyzed: step change, linear and polynomial gradients. In addition to localize the deformation in the interface, three different flexure designs in the interface are analyzed. This paper will address a methodology for modeling and parametrization of material properties and transition at the interface, for different flexure designs. The combined effort in the interface of the functional grading and the geometry will be used for the design of monolithic self-deployable structures, initially folded in compact shape. The design motivation comes from the self-deploying mechanisms inspired by insects’ wings.